Endoplasmic Reticulum Stress-induced Transcriptional Factor CHOP and Cardiovascular Diseases - Gotoh, Tomomi; Endo, Motoyoshi; Oike, Yuichi (Current Hypertension Reviews, 2010)
The endoplasmic reticulum (ER) is the site of synthesis and maturation of proteins, designed for secretion, and the cell membrane. Various types of stress from both inside and outside of cells disturb ER function, and unfolded or misfolded proteins accumulate in the ER. The accumulation of these abnormal proteins in the ER further disturbs ER function and cell survival can be threatened. To improve and maintain ER functions against such stress, the ER stress response pathway is activated. When the stress is too severe to maintain ER function, apoptosis pathways are activated to remove damaged cells to protect organs and the whole body. However, when a large number of cells are lost through apoptosis, disturbance of organ function is induced. Therefore, ER stress-induced apoptosis is involved in various diseases, including diabetes, ischemic diseases, atherosclerosis, and heart failure. The transcription factor CHOP/GADD153 is induced by ER stress, and is involved in ER stress-induced apoptosis. CHOP is a member of the CCAAT/enhancer binding proteins (C/EBPs), and forms heterodimers with other C/EBP family members, and binds to the CHOP-binding site of DNA, which is distinct from the C/EBP-binding site. CHOP is also involved in the process of inflammation, through the activation of pro-IL-1β. The pathological roles of CHOP therefore remain to be further investigated.
Keywords: inflammation